The portrait of good governance of Islamic philanthropic institutions in achieving the SDGs - Kholmi, Masiyah; Jati, Ahmad Waluya; Suhardi, Diding (Universitas Muhammadiyah Yogyakarta, Indonesia, 2026)
Research aims: This study aims to analyze the governance of Amil Zakat Muhammadiyah (LAZISMU) in East Java in achieving sustainable development goals (SDGs).Design/Methodology/Approach: This study uses a qualitative approach with semi-structural and Focus Group Discussion (FGD) interview techniques with leaders in three LAZISMU regions in the East Java region.Research findings: This study shows that zakat institutions have served as an Islamic philanthropic institution. LAZISMU East Java managed to overcome poverty, community economic impurity and improve welfare. Good governance has a role in encouraging the realization of SDGs, namely, transparency, accountability and trust or integrity. In addition, discipline or obedience, efficiency and effectiveness, independent, innovative, justice, participation, professionalism and responsive. LAZISMU has achieved sustainable development goals (SDGs) as follows: Poverty Alleviation (1), Decent Work and Economic Growth (8), Qualified Education (4), Health Service (3), Social Humanity [Zero Hunger (2), Reduced Inequalities (10) and Climate Action (13)], Welfare of society (ummah) [(peace justice, and strong institutions (16) and partenships for the goals (17)]. The study also found challenges in the application of governance, such as HR limitations, brought together the pattern of governance between institutions in various regions of the research object.Theoretical contribution/Originality: This study contributes to enriching governance literature and the role of Zakat institutions in achieving sustainable development goals (SDGs).Practitioner/Policy implication: This study emphasizes the importance of governance in the management of zakat institutions in achieving SDGs and the need for greater support from the National Amil Zakat (BAZNAS).Research limitation/Implication: This study has limitations, in three LAZISMU in the East Java region. In addition, data collection is only through deep interviews and FGD.